Future changes, or lack thereof, in the temporal variability of the combined wind-plus-solar power production in Europe. (August 2019) - Jerez, S.; Tobin, I.; Turco, M.; Jiménez-Guerrero, P.; Vautard, R.; Montávez, J.P.
Abstract: Here we present the first assessment of climate change impacts on the temporal variability of the joint production of wind and solar photovoltaic (PV) power across Europe. For that we adopted regional and continental perspectives (assuming a single European electricity grid), considered several temporal frequencies (from daily to annual), used state-of-the-art regional climate projections together with a climate-production model, and assumed a future massive deployment of wind and PV power installations. Results support that the spatio-temporal complementarity between the wind and solar resources helps to minimize the temporal variability of the combined production under both present (1971–2000) and future (2070–2099) climate conditions similarly. Thus the projected changes are overall negligible (well below ±5%). However, an additional assessment of theoretical upper/bottom bounds for these changes indicated significant potential increases in the stability of the joint production ranging from 5 to 25% across regions, 15% at the continental scale. This would be subordinated to the feasibility of reaching, with the future deployment strategies, individual wind and PV power production series with a perfect temporal anticorrelation. These results may encourage stakeholders to take holistically optimized decisions. Highlights: Spatio-temporal complementarity between wind and solar resources drops the variability of the mix production similarly under present and future climates. Climate change impacts little on the stability of the combined PV-plus-wind power production. Stability could grow up to 15% at the European continental scale (5 to 25% across regions) by exploiting the spatio-temporal complementarity of the resources.